Double-phase reinforced titanium-based composite material and preparation method thereof
By melting TiB2 and Si powders with TC4 titanium alloy in a vacuum non-consumable arc furnace to form TiB and Ti5Si3 reinforcing phases, the problem of low uniformity in the preparation of titanium-based composite materials was solved, and higher hardness, strength and elastic modulus were achieved, thus expanding the application range.
Patent Information
- Application Number
- CN202411174255.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-01-10
AI Technical Summary
Existing biphase reinforced titanium matrix composites suffer from low uniformity in preparation, which affects their mechanical properties and application range.
TiB2 and Si powders were smelted with TC4 titanium alloy in a vacuum non-consumable arc furnace to form TiB and Ti5Si3 reinforcing phases. Primary and secondary network structures were formed through in-situ reactions, thus optimizing the distribution of the reinforcing phases.
It improves the uniformity of titanium-based composite material preparation and the overall mechanical properties, enhances the material's hardness, strength and elastic modulus, and broadens its application in high-temperature fields.
Smart Images

Figure CN119287212A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium-based composite materials, and in particular to a dual-phase reinforced titanium-based composite material and a preparation method thereof. Background Art
[0002] Titanium-based composite materials have the advantages of high specific strength, high specific modulus, low density, good biocompatibility, heat resistance and wear resistance, which makes them have broad application prospects in aerospace, advanced weapon systems, nuclear industry and automobile fields.
[0003] In the selection of reinforcing phase, Al2O3 is one of the commonly used reinforcing phases in the previous research on metal-based composites, but it is easy to react with the more active Ti, resulting in a more serious interface reaction. Therefore, this type of reinforcing phase has rarely been used in the research of titanium-based composites in recent years. Studies have shown that the morphology of TiC is related to the preparation process and the content of C, which will affect the mechanical properties of the composite. The characteristics of TiB make it an ideal reinforcing phase for titanium-based composites. In the process of in-situ preparation of TMCs, Ti5Si3 is rarely used as a reinforcement. Ti5Si3 has many excellent properties, such as low density, high melting point, and a thermal expansion coefficient that is close to that of Ti alloys. Due to its high hardness, special chemical composition and strong covalent bonds, Ti5Si3 can also be used as a wear-resistant and corrosion-resistant material. In summary, it can be seen that Ti5Si3-enhanced TMCs will improve the high-temperature comprehensive performance of composites and broaden their applications in high-temperature fields. The titanium-based composites prepared with TiB2 as the B source have excellent mechanical properties and can significantly improve the tensile strength and wear resistance of the composites at high temperature and room temperature.
[0004] This paper mainly studies the influence of the distribution of reinforcement on the reinforcement effect of the matrix. In order to avoid the influence of TiC, TiB2 is selected as the B source to prepare titanium-based composites. Summary of the invention
[0005] In order to solve the problem of low preparation uniformity of existing dual-phase reinforced titanium-based composite materials, the present invention provides a dual-phase reinforced titanium-based composite material and a preparation method thereof.
[0006] According to a first aspect of the present invention, the present invention provides a dual-phase reinforced titanium-based composite material, comprising, by mass percentage:
[0007] 0.5-2.2wt.% Si, 1.4-2.1wt.% TiB2, the remainder is TC4 titanium alloy, and the sum of the weight percentages of the above components is 100%; the base phase of the dual-phase reinforced titanium-based composite material is Ti phase, the Ti phase includes β-Ti phase and α-Ti phase, and TiB reinforcing phase is distributed around the Ti phase to form a primary network structure; Ti5Si3 reinforcing phase is distributed in the β-Ti phase, and the β-Ti phase forms a secondary network structure around the α-Ti phase; the average diameter of the network unit in the secondary network structure is 5-10μm, and the average diameter of the network unit in the secondary network structure is 10-40μm.
[0008] Preferably, the content of Si is 1.1-2wt.%, and the content of TiB2 is 1.4-1.9wt.%.
[0009] Preferably, the content of Si is 1.1-1.2wt.%, the content of TiB2 is 1.4-1.5wt.%, and the balance is TC4 titanium alloy, and the sum of the weight percentages of the above components is 100%.
[0010] Preferably, the shape of the TiB reinforcement phase includes a rod shape, and the average size of the TiB reinforcement phase is 2-10 μm; the shape of the Ti5Si3 reinforcement phase includes a rod shape, and the average size of the Ti5Si3 reinforcement phase is 200-800 nm.
[0011] Preferably, the compressive strength of the dual-phase reinforced titanium-based composite material is 1802-2005 MPa, and the compression plasticity is 17.04-25.17%.
[0012] Preferably, the compressive strength of the dual-phase reinforced titanium-based composite material is 1853-2005 MPa, and the compression plasticity is 23.74-25.17%.
[0013] Preferably, the powder particle size of the TiB2 is 1 to 2 μm; the powder particle size of the Si is 100 to 800 nm.
[0014] Preferably, the Al content of the TC4 titanium alloy is 5.5-6.8%, the V content is 3.5-4.5%, the Fe content is 0-0.30%, the O content is 0-0.20%, the C content is 0-0.15%, the N content is 0-0.05%, the H content is 0-0.015%, and the remainder is Ti. The sum of the weight percentages of the components of the TC4 titanium alloy is 100%.
[0015] According to a second aspect of the present invention, the present invention provides a method for preparing a dual-phase reinforced titanium-based composite material, comprising the following steps:
[0016] Si powder, TiB2 powder and TC4 titanium alloy are smelted together, during which Si and TiB2 react in situ with the Ti-based phase of the TC4 titanium alloy to form a TiB reinforcement phase and a Ti5Si3 reinforcement phase, and the dual-phase reinforced titanium-based composite material obtained after the smelting contains the TiB reinforcement phase and the Ti5Si3 reinforcement phase;
[0017] The volume percentage of the dual-phase reinforced titanium-based composite material is (xvol.%Ti5Si3+3vol.%TiB) / TC4, wherein x=2-8.
[0018] Preferably, the smelting includes a first smelting and a second smelting;
[0019] The first smelting includes placing the Si powder, TiB2 powder and TC4 titanium alloy in a vacuum non-consumable arc furnace to obtain a first smelt;
[0020] The second smelting includes placing the first smelt in the vacuum non-consumable arc furnace for front and back alternating smelting, and the number of front and back alternating smelting is 5-6 times.
[0021] The present invention has the following advantages:
[0022] 1. In the present invention, the TiBw reinforcement phase is distributed around the TC4 original particles to form a primary network structure, and the Ti5Si3 reinforcement phase is distributed in the β-Ti phase to form a bipolar network structure around the α-Ti, thereby achieving a dual-phase reinforcement effect and improving the preparation uniformity of the dual-phase reinforced titanium-based composite material.
[0023] 2. The present invention reduces the cost by selecting TiB2 powder, Si powder and TC4 matrix to prepare in situ and prepare a two-level network structure (Ti5Si3+TiBw) / Ti6Al4V composite material, and obtains a titanium-based composite material with higher comprehensive mechanical properties through effective regulation of the reinforcing phase.
[0024] 3. The present invention solves the shortcomings of low surface strength and small elastic modulus of titanium alloy matrix by forming a reinforcing phase in the TC4 base phase. At the same time, the hardness, strength, melting point and elastic modulus of titanium-based composite materials are improved. By selecting materials that are appropriately matched with the base alloy in terms of physical and chemical properties, and the interface reaction between the reinforcing phase and the base will affect the use and processing of the metal-based composite material, it is therefore selected to have excellent mechanical properties, excellent physical properties, a thermal expansion coefficient close to that of the titanium alloy base, a strong bond with the titanium base, and a thin and uniform interface reaction zone between the reinforcing phase and the base. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1The XRD analysis of the composite materials with different compositions (Ti5Si3+TiB) / Ti6Al4V of the present invention is shown;
[0026] Figure 2 The microhardness diagram of the composite material with different compositions (Ti5Si3+TiB) / Ti6Al4V of the present invention is shown;
[0027] Figure 3 The room temperature compression performance diagram of the composite material with different compositions (Ti5Si3+TiB) / Ti6Al4V of the present invention is shown;
[0028] Figure 4 The microstructure of the composite material (2 vol.% Ti5Si3 + 3 vol.% TiB) / Ti6Al4V of the present invention is shown;
[0029] Figure 5 The microstructure of the composite material (4 vol.% Ti5Si3+3 vol.% TiB) / Ti6Al4V of the present invention is shown;
[0030] Figure 6 The microstructure of the composite material (6 vol.% Ti5Si3 + 3 vol.% TiB) / Ti6Al4V of the present invention is shown;
[0031] Figure 7 The microstructure of the composite material (8 vol.% Ti5Si3 + 3 vol.% TiB) / Ti6Al4V of the present invention is shown;
[0032] Figure 8 The microstructure of the (0 vol.% Ti5Si3+3 vol.% TiB) / Ti6Al4V composite material of the present invention is shown. DETAILED DESCRIPTION
[0033] The present disclosure will now be discussed with reference to several exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and thus implement the present disclosure, rather than implying any limitation on the scope of the present disclosure.
[0034] In the first aspect, this embodiment discloses a dual-phase reinforced titanium-based composite material, such as Figure 1 As shown, in terms of mass percentage, it includes:
[0035] 0-2.2wt.% Si, 1.4-2.1wt.% TiB2, the remainder is TC4 titanium alloy, and the sum of the weight percentages of the above components is 100%; the base phase of the dual-phase reinforced titanium-based composite material is Ti phase, the Ti phase includes β-Ti phase and α-Ti phase, and TiB reinforcing phase is distributed around the Ti phase to form a primary network structure; Ti5Si3 reinforcing phase is distributed in the β-Ti phase, and the β-Ti phase forms a secondary network structure around the α-Ti phase; the average diameter of the network units in the secondary network structure is 5-10μm, and the average diameter of the network units in the secondary network structure is 10-40μm.
[0036] Preferably, the content of Si is 1.1-2wt.%, and the content of TiB2 is 1.4-1.9wt.%.
[0037] Preferably, the content of Si is 1.1-1.2wt.%, the content of TiB2 is 1.4-1.5wt.%, and the balance is TC4 titanium alloy, and the sum of the weight percentages of the above components is 100%.
[0038] Preferably, the shape of the TiB reinforcement phase includes a rod shape, and the average size of the TiB reinforcement phase is 2-10 μm; the shape of the Ti5Si3 reinforcement phase includes a rod shape, and the average size of the Ti5Si3 reinforcement phase is 200-800 nm.
[0039] Preferably, the compressive strength of the dual-phase reinforced titanium-based composite material is 1802-2005 MPa, and the compression plasticity is 17.04-25.17%.
[0040] Preferably, the powder particle size of the TiB2 is 1 to 2 μm, the average particle size is 1 μm, and the purity of the TiB2 powder is 99.99%; the powder particle size of the Si is 100 to 800 nm, the average particle size is 800 nm, and the purity of the Si powder is 99%.
[0041] Preferably, the Al content of the TC4 titanium alloy is 5.5-6.8%, the V content is 3.5-4.5%, the Fe content is 0-0.30%, the O content is 0-0.20%, the C content is 0-0.15%, the N content is 0-0.05%, the H content is 0-0.015%, and the remainder is Ti. The sum of the weight percentages of the components of the TC4 titanium alloy is 100%.
[0042] In a second aspect, this embodiment provides a method for preparing a dual-phase reinforced titanium-based composite material, comprising the following steps:
[0043] Si powder, TiB2 powder and TC4 titanium alloy are smelted together, during which Si and TiB2 react in situ with the Ti-based phase of the TC4 titanium alloy to form a TiB reinforcement phase and a Ti5Si3 reinforcement phase, and the dual-phase reinforced titanium-based composite material obtained after the smelting contains the TiB reinforcement phase and the Ti5Si3 reinforcement phase;
[0044] The volume percentage of the dual-phase reinforced titanium-based composite material is (xvol.%Ti5Si3+3vol.%TiB) / TC4, wherein x=2-8.
[0045] Preferably, the smelting includes a first smelting and a second smelting;
[0046] The first smelting includes placing the Si powder, TiB2 powder and TC4 titanium alloy in a vacuum non-consumable arc furnace to obtain a first smelt;
[0047] The second smelting includes placing the first smelt in the vacuum non-consumable arc furnace for front and back alternating smelting, and the number of front and back alternating smelting is 5-6 times.
[0048] Example 1
[0049] 1) Industrial TC4 titanium alloy, TiB2 powder and Si powder are selected as raw materials, and the mass percentage (wt.%) of TMCs-2 components are: 0.5-0.6wt.% Si, 1.4-1.5wt.% TiB2, and the balance is TC4; a vacuum non-consumable arc furnace is used for smelting to obtain a TC4-based composite material; then the TC4-based composite material is repeatedly smelted 5-6 times on the front and back sides alternately, and each side of the front and back sides of a part is smelted for 6 minutes respectively, and the smelting temperature is 2500°C. Specifically, a part needs to be repeatedly smelted 10-12 times to obtain a TC4-based composite material sample, that is, a composite material sample with a composition volume percentage of (2vol.%Ti5Si3+3vol.%TiB) / TC4, and a mass percentage of 3.017wt.%TiB and 1.85wt.%Ti5Si3;
[0050] The phase analysis of (2vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material was carried out by X-ray diffractometer. Figure 1 As shown in Figure 2, the TC4-based composite material is mainly composed of Ti phase, TiB phase, and Ti5Si3 phase, without any other phases.
[0051] The microstructure of the (2vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material was observed using a SEM electron microscope. Figure 4 As shown by Figure 4 It can be seen that the TiBw (w stands for whisker, the same below) reinforcement phase is distributed around the Ti6Al4V original particles to form a primary network structure. A small amount of Ti5Si3 reinforcement phase is distributed in the β-Ti phase, and the β-Ti phase forms a secondary network structure around the α-Ti. Although the reinforcement phase is relatively uniformly distributed, the size distribution of the reinforcement phase is uneven. Among them, the Ti5Si3 reinforcement phase is rod-shaped with an average size of 200nm; the TiB reinforcement phase is rod-shaped with an average size of 5 to 8μm.
[0052] The hardness of the composite material was measured using a HR-150A Rockwell hardness tester. The final hardness value of each sample was the average of the results of 5 tests. In addition, before the test, the sample was polished with sandpaper and mechanically polished until there were no scratches on the surface of the sample and it finally appeared in a mirror state. Figure 2 As shown in Figure 2, the Rockwell hardness of TMCs-2 is 54.67HRC.
[0053] The (2 vol. % Ti5Si3 + 3 vol. % TiB) / Ti6Al4V composite material was processed into standard specimens according to the national standard GB / T228.1-2010, and then subjected to room temperature compression test on MTS810 electronic universal testing machine. The compression strain rate was 1.38×10 -4 s -1 Among them, the room temperature compressive strength is 1853MPa, the compression plasticity is 23.74%, and the room temperature compression test performance is as follows Figure 3 shown.
[0054] Example 2
[0055] 1) Industrial TC4 titanium alloy, TiB2 powder and Si powder are selected as raw materials, and the mass percentage (wt.%) of TMCs-3 components are: 1.1-1.2wt.% Si, 1.4-1.5wt.% TiB2, and the balance is TC4; a vacuum non-consumable arc furnace is used for smelting to obtain a TC4-based composite material; then the TC4-based composite material is repeatedly smelted 5-6 times on the front and back sides alternately, and each side of the front and back sides of a part is smelted for 6 minutes respectively, and the smelting temperature is 2500°C. Specifically, a part needs to be repeatedly smelted 10-12 times to obtain a TC4-based composite material sample, that is, a composite material sample with a composition volume percentage of (4vol.%Ti5Si3+3vol.%TiB) / TC4, and a mass percentage of 3.017wt.%TiB and 3.67wt.%Ti5Si3;
[0056] The phase analysis of (4vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material was carried out by X-ray diffractometer. Figure 1As shown in Figure 2, the TC4-based composite material is mainly composed of Ti phase, TiB phase, and Ti5Si3 phase, without any other phases.
[0057] The microstructure of the (4vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material was observed using a SEM electron microscope. Figure 5 As shown by Figure 5 It can be seen that the TiBw reinforcement phase is distributed around the Ti6Al4V original particles to form a primary network structure. The Ti5Si3 reinforcement phase is distributed in the β-Ti phase, and the β-Ti phase forms a secondary network structure around the α-Ti. Its organizational distribution is more uniform, forming a near-network structure distribution. The Ti5Si3 reinforcement phase is rod-shaped with an average size of 400nm; the TiB reinforcement phase is rod-shaped with an average size of 4 to 10μm.
[0058] The hardness of the composite material was measured using a HR-150A Rockwell hardness tester. The final hardness value of each sample was the average of the results of 5 tests. In addition, before the test, the sample was polished with sandpaper and mechanically polished until there were no scratches on the surface of the sample and it finally appeared in a mirror state. Figure 2 As shown in Figure 2. Among them, the Rockwell hardness of TMCs-3 is 59.33HRC.
[0059] The (4 vol. % Ti5Si3+3 vol. % TiB) / Ti6Al4V composite material was processed into standard specimens according to the national standard GB / T228.1-2010, and then subjected to room temperature compression test on MTS810 electronic universal testing machine. The compression strain rate was 1.38×10 -4 s -1 Among them, the room temperature compressive strength is 2005MPa, the compression plasticity is 25.17%, and the room temperature compression test performance is as follows Figure 3 shown.
[0060] Example 3
[0061] 1) Industrial TC4 titanium alloy, TiB2 powder and Si powder are selected as raw materials, and the mass percentage (wt.%) of TMCs-4 components are: 1.6-1.7wt.% Si, 1.9-2.1wt.% TiB2, and the balance is TC4; a vacuum non-consumable arc furnace is used for smelting to obtain a TC4-based composite material; then the TC4-based composite material is repeatedly smelted 5-6 times on the front and back sides alternately, and each side of the front and back sides of a part is smelted for 6 minutes respectively, and the smelting temperature is 2500°C. Specifically, a part needs to be repeatedly smelted 10-12 times to obtain a TC4-based composite material sample, that is, a composite material sample with a composition volume percentage of (6vol.%Ti5Si3+3vol.%TiB) / TC4, and a mass percentage of 3.017wt.%TiB and 5.4wt.%Ti5Si3;
[0062] The phase analysis of (6vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material was carried out by X-ray diffractometer. Figure 1 As shown in Figure 2, the TC4-based composite material is mainly composed of Ti phase, TiB phase, and Ti5Si3 phase, without any other phases.
[0063] The microstructure of the (6vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material was observed using a SEM electron microscope. Figure 6 As shown by Figure 6 It can be seen that the TiBw reinforcement phase is distributed around the Ti6Al4V original particles to form a primary network structure. More Ti5Si3 reinforcement phases are distributed in the β-Ti phase, and the β-Ti phase is formed around the α-Ti. As the number of Ti5Si3 reinforcement phases increases, its aggregation phenomenon becomes more serious. The Ti5Si3 reinforcement phase is rod-shaped with an average size of 600nm; the TiB reinforcement phase is rod-shaped with an average size of 2 to 4μm.
[0064] The hardness of the composite material was measured using a HR-150A Rockwell hardness tester. The final hardness value of each sample was the average of the results of 5 tests. In addition, before the test, the sample was polished with sandpaper and mechanically polished until there were no scratches on the surface of the sample and it finally appeared in a mirror state. Figure 2 As shown in Figure 2. Among them, the Rockwell hardness of TMCs-4 is 56HRC.
[0065] The (6 vol. % Ti5Si3 + 3 vol. % TiB) / Ti6Al4V composite material was processed into standard specimens according to the national standard GB / T228.1-2010, and then subjected to room temperature compression test on an MTS810 electronic universal testing machine. The compression strain rate was 1.38×10 -4 s -1Among them, the room temperature compressive strength is 1802MPa, the compression plasticity is 20.14%, and the room temperature compression test performance is as follows Figure 3 shown.
[0066] Example 4
[0067] 1) Industrial TC4 titanium alloy, TiB2 powder and Si powder are selected as raw materials, and the mass percentage (wt.%) of TMCs-5 components are: 2-2.2wt.% Si, 1.9-2.1wt.% TiB2, and the balance is TC4; a vacuum non-consumable arc furnace is used for smelting to obtain a TC4-based composite material; then the TC4-based composite material is repeatedly smelted 5-6 times on the front and back sides alternately, and each side of the front and back sides of a part is smelted for 6 minutes respectively, and the smelting temperature is 2500°C. Specifically, a part needs to be repeatedly smelted 10-12 times to obtain a TC4-based composite material sample, that is, a composite material sample with a volume percentage of (8vol.%Ti5Si3+3vol.%TiB) / TC4, and a mass percentage of 3.017wt.%TiB and 7.54wt.%Ti5Si3;
[0068] The phase analysis of (8vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material was carried out by X-ray diffractometer. Figure 1 As shown in Figure 2, the TC4-based composite material is mainly composed of Ti phase, TiB phase, and Ti5Si3 phase, without any other phases.
[0069] The microstructure of the (8vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material was observed using a SEM electron microscope. Figure 7 As shown by Figure 7 It can be seen that the TiBw reinforcement phase is distributed around the Ti6Al4V original particles to form a primary network structure. More Ti5Si3 reinforcement phase is distributed in the β-Ti phase, and the β-Ti phase is formed around the α-Ti. When the reinforcement phase content is too much, the organization aggregation phenomenon is too serious, resulting in irregular organization. The Ti5Si3 reinforcement phase is rod-shaped with an average size of 800nm; the TiB reinforcement phase is rod-shaped with an average size of 8 to 10μm.
[0070] The hardness of the composite material was measured using a HR-150A Rockwell hardness tester. The final hardness value of each sample was the average of the results of 5 tests. In addition, before the test, the sample was polished with sandpaper and mechanically polished until there were no scratches on the surface of the sample and it finally appeared in a mirror state. Figure 2 As shown in Figure 2. Among them, the Rockwell hardness of TMCs-5 is 56.67HRC.
[0071] The (8 vol. % Ti5Si3 + 3 vol. % TiB) / Ti6Al4V composite material was processed into standard specimens according to the national standard GB / T228.1-2010, and then subjected to room temperature compression test on an MTS810 electronic universal testing machine. The compression strain rate was 1.38×10 -4 s -1 Among them, the room temperature compressive strength is 1887MPa, the compression plasticity is 17.04%, and the room temperature compression test performance is as follows Figure 3 shown.
[0072] Comparative Example 1
[0073] 1) Industrial TC4 titanium alloy and TiB2 powder are selected as raw materials, and the mass percentage (wt.%) of TMCs-1 components is: 2-2.2wt.% TiB2, and the balance is TC4; a vacuum non-consumable arc furnace is used for smelting to obtain a TC4-based composite material; then the TC4-based composite material is repeatedly smelted 5-6 times on the front and back sides alternately, and each of the front and back sides of a part is smelted for 6 minutes, and the smelting temperature is 2500°C. Specifically, a part needs to be repeatedly smelted 10-12 times to obtain a TC4-based composite material sample, that is, a composite material sample with a volume percentage of (0vol.%Ti5Si3+3vol.%TiB) / TC4 and a mass percentage of 3.017wt.%TiB;
[0074] The phase analysis of (0vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material was carried out by X-ray diffractometer. Figure 1 As shown in Figure 2, the TC4-based composite material is mainly composed of Ti phase and TiB phase, without any other phases.
[0075] The microstructure of the (0 vol.% Ti5Si3+3 vol.% TiB) / Ti6Al4V composite material was observed using a SEM electron microscope. Figure 8 As shown by Figure 8 It can be seen that the TiBw reinforcement phase is distributed around the Ti6Al4V original particles to form a primary network structure, and the single-phase reinforced titanium-based composite material has dense organization and aggregation. The TiB phase is rod-shaped with an average size of 1 to 4 μm.
[0076] The hardness of the composite material was measured using a HR-150A Rockwell hardness tester. The final hardness value of each sample was the average of the results of 5 tests. In addition, before the test, the sample was polished with sandpaper and mechanically polished until there were no scratches on the surface of the sample and it finally appeared in a mirror state. Figure 2 As shown in Figure 1, the Rockwell hardness of TMCs-1 is 52.33HRC.
[0077] The (0 vol.%Ti5Si3+3 vol.%TiB) / Ti6Al4V composite material was processed into standard specimens according to the national standard GB / T228.1-2010, and then subjected to room temperature compression test on MTS810 electronic universal testing machine. The compression strain rate was 1.38×10 -4 s -1 Among them, the room temperature compressive strength is 1550MPa, the compression plasticity is 20.17%, and the room temperature compression test performance is as follows Figure 3 shown.
[0078] The performance of the TC4 composite material obtained according to Examples 1-4 of the present invention is higher than that of the TC4 composite material obtained in Comparative 1 to a certain extent, as shown in Table 1:
[0079] Table 1 Performance of Examples 1-4 and Comparative Example 1
[0080]
[0081]
[0082] As shown in Table 1, the compressive strength of Examples 1-4 is greater than that of Comparative Example 1, the compression plasticity of Examples 1 and 2 is greater than that of Comparative Example 1, and the compression plasticity of Examples 3 and 4 is less than that of Comparative Example 1. The addition of Ti5Si3 reinforcement phase better forms a secondary network structure, thereby improving the Rockwell hardness and compressive strength of the composite material, but too much reinforcement phase addition has a bad effect on its compression plasticity. As shown in Table 1, in Example 2, i.e. (4vol.%Ti5Si3+3vol.%TiB) / Ti6Al4V composite material, its compression plasticity is the best at this time, which indicates that the reinforcement phase content is added best at this time. In summary, the present invention improves the mechanical properties of the material by changing the reinforcement phase content of different components, exerts the synergistic strengthening effect of the two reinforcement phases, realizes the strong plasticity matching of the titanium-based composite material, and finally improves the mechanical properties of the titanium-based composite material to realize the strong plasticity matching of the titanium-based composite material. Among them, Example 2 has the best performance, and its room temperature compressive strength reaches 2005MPa and its compression plasticity reaches 25.17%. The raw materials of the invention are widely available and inexpensive, the preparation process is simple and the cycle is short, and it is conducive to realizing large-scale industrial production.
[0083] Those skilled in the art will appreciate that the above-mentioned embodiments are specific examples for implementing the present disclosure, and in actual applications, various changes may be made thereto in form and detail without departing from the scope of the present disclosure.
Claims
1. A dual-phase reinforced titanium-based composite material, characterized in that: Included by mass percentage: 0.5-2.2wt.% Si, 1.4-2.1wt.% TiB2, the remainder is TC4 titanium alloy, and the sum of the weight percentages of the above components is 100%; the base phase of the dual-phase reinforced titanium-based composite material is Ti phase, the Ti phase includes β-Ti phase and α-Ti phase, and TiB reinforcing phase is distributed around the Ti phase to form a primary network structure; Ti5Si3 reinforcing phase is distributed in the β-Ti phase, and the β-Ti phase forms a secondary network structure around the α-Ti phase; the average diameter of the network units in the secondary network structure is 5-10μm, and the average diameter of the network units in the secondary network structure is 10-40μm.
2. A dual-phase reinforced titanium-based composite material according to claim 1, characterized in that: The content of Si is 1.1-2 wt.%, and the content of TiB2 is 1.4-1.9 wt.%.
3. A dual-phase reinforced titanium-based composite material according to claim 1, characterized in that: The content of Si is 1.1-1.2 wt.%, and the content of TiB2 is 1.4-1.5 wt.%.
4. A dual-phase reinforced titanium-based composite material according to claim 1, characterized in that: The shape of the TiB reinforcement phase includes a rod shape, and the average size of the TiB reinforcement phase is 2-10 μm; the shape of the Ti5Si3 reinforcement phase includes a rod shape, and the average size of the Ti5Si3 reinforcement phase is 200-800 nm.
5. The dual-phase reinforced titanium-based composite material according to claim 1, characterized in that: The compressive strength of the dual-phase reinforced titanium-based composite material is 1802-2005Mpa, and the compression plasticity is 17.04-25.17%.
6. The dual-phase reinforced titanium-based composite material according to claim 1, characterized in that: The dual-phase reinforced titanium-based composite material has a compressive strength of 1853-2005 MPa and a compression plasticity of 23.74-25.17%.
7. The dual-phase reinforced titanium-based composite material according to claim 1, characterized in that: The powder particle size of the TiB2 is 1 to 2 μm; the powder particle size of the Si is 100 to 800 nm.
8. The dual-phase reinforced titanium-based composite material according to claim 1, characterized in that: The TC4 titanium alloy comprises 5.5-6.8% Al, 3.5-4.5% V, 0-0.30% Fe, 0-0.20% O, 0-0.15% C, 0-0.05% N, 0-0.015% H, and the remainder is Ti. The sum of the weight percentages of the components of the TC4 titanium alloy is 100%.
9. A method for preparing a dual-phase reinforced titanium-based composite material, characterized in that: The steps include: Si powder, TiB2 powder and TC4 titanium alloy are smelted together, during which Si and TiB2 react in situ with the Ti-based phase of the TC4 titanium alloy to form a TiB reinforcement phase and a Ti5Si3 reinforcement phase, and the dual-phase reinforced titanium-based composite material obtained after the smelting contains the TiB reinforcement phase and the Ti5Si3 reinforcement phase; The volume percentage of the dual-phase reinforced titanium-based composite material is (xvol.%Ti5Si3+3vol.%TiB) / TC4, wherein x=2-8.
10. The method for preparing a dual-phase reinforced titanium-based composite material according to claim 9, characterized in that: The smelting includes a first smelting and a second smelting; The first smelting includes placing the Si powder, TiB2 powder and TC4 titanium alloy in a vacuum non-consumable arc furnace to obtain a first smelt; The second smelting includes placing the first smelt in the vacuum non-consumable arc furnace for front and back alternating smelting, and the number of front and back alternating smelting is 5-6 times.
Citation Information
Cited By
Preparation method of SiCf / TiB / Ti2AlNb composite material with double reinforcement phases of different scales
CN121250266A